Optimal taxation and public provision for poverty reduction - Ravi Kanbur; Jukka Pirttilä; Matti Tuomala; Tuuli Ylinen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
The existing literature on optimal taxation typically assumes there exists a capacity to implement complex tax schemes, which is not necessarily the case for many developing countries. We examine the determinants of optimal redistributive policies in the context of a developing country that can only implement linear tax policies due to administrative reasons. Further, the reduction of poverty is typically the expressed goal of such countries, and this feature is also taken into account in our model. We derive the optimality conditions for linear income taxation, commodity taxation, and public provision of private and public goods for the poverty minimization case, and compare the results to those derived under a general welfarist objective function. We also study the implications of informality on optimal redistributive policies for such countries, and comment on the potential for minimum wage regulation. The exercise reveals nontrivial differences in optimal tax rules under the different assumptions. The derived formulae also capture the sufficient statistics that the governments need to pay attention to when designing poverty alleviation policies.
Keywords: H21; H40; O12; 330; redistribution; income taxation; commodity taxation; public good provision; poverty